Professional knowledge and rural school: reflections on the teachers' voice - Francisca Maísa Maciel Gomes de Almeida; Simone Cabral Marinho dos Santos; Taysa Kelly da Silva (Universidade Federal do Norte do Tocantins, 2020)
One of the great contributions of (new) Rural Education is the recognition of the need for knowledge and teaching skills forged in unique and singular experiences, both in their training process and in the daily activities of their activities as teachers. This article aims to reflect on the professional knowledge of teachers who work in rural schools, built, related and mobilized by teachers according to the demands and challenges arising from this educational reality. This is a field study, within a qualitative approach, carried out through the application of semi-structured interviews with four teachers who work in a rural school. We combine empirical research with the epistemological model of understanding and analysis for teachers' knowledge presented by Tardif (2011), translated into professional knowledge, disciplinary knowledge, curricular knowledge and experiential knowledge. The results of the research reveal that teachers value experiential knowledge, without disparaging professional knowledge, because, without specific training to work in the rural school, it is in their daily tasks that they experience concrete situations, from which it is necessary decide the strategies and actions in view of the situation presented.